If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 9) = 9 + -2(x + -9) Reorder the terms: 3(9 + 3x) = 9 + -2(x + -9) (9 * 3 + 3x * 3) = 9 + -2(x + -9) (27 + 9x) = 9 + -2(x + -9) Reorder the terms: 27 + 9x = 9 + -2(-9 + x) 27 + 9x = 9 + (-9 * -2 + x * -2) 27 + 9x = 9 + (18 + -2x) Combine like terms: 9 + 18 = 27 27 + 9x = 27 + -2x Add '-27' to each side of the equation. 27 + -27 + 9x = 27 + -27 + -2x Combine like terms: 27 + -27 = 0 0 + 9x = 27 + -27 + -2x 9x = 27 + -27 + -2x Combine like terms: 27 + -27 = 0 9x = 0 + -2x 9x = -2x Solving 9x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9x + 2x = -2x + 2x Combine like terms: 9x + 2x = 11x 11x = -2x + 2x Combine like terms: -2x + 2x = 0 11x = 0 Divide each side by '11'. x = 0 Simplifying x = 0
| 21p=819 | | s=bd-9 | | r/11=20 | | 3/8-5/15 | | 2c+8=-10c | | y=2x+45 | | 23-5x=32 | | 6-9x=7x+8 | | 3(5+x)=3 | | 88-1/3x9 | | 24=s/-22 | | 4-x-3x=-8 | | 3/4w-12w-4=12 | | 2x-4(3-2x)=4(x-5)-28 | | 150w+2=195w+1 | | 432=27v | | 6y/2y | | 8-.6(6-15-7)+7= | | 7/(2/3) | | y+1=16 | | y6^6/y^2 | | v+33=869 | | 8-6.6(6-15-7)+7= | | 150+2=195+1 | | -4(1+m)=4-2m | | -3=4(3x-2)+1 | | 21=s/10 | | 5(b-1)=-20 | | 3(1-8x)=35-8x | | 8-6.7(6-15-7)+7= | | 5x-(4x+3)+6=8 | | -896=905 |